West African ‘Stone Boys’ in the Ibadan Mining Frontiers Since the 1990s (2014)
In the last two decades of the 20th century, the city of Ibadan, capital of Oyo state, Nigeria hosted migrant entrepreneurs, “stone boys "from the West African sub-region who were actively involved in the export of gemstones. This paper drew on fieldwork to explicate how culture of migration, prevalent among West Africans, intertwined with entrepreneurship in the international gemstones trade and its implications on the Nigerian economy. It argued that gemstones trade among West African m igrants was an inherited commercial heritage. It further advanced that lack of government investment in the non-oil solid mineral sector provided a leewayfor artisanal miners and unregulated export of gemstones; and social solidarity and identity empowered the migrants to dominate the export of gemstones.